‘Sacred or profane?’: motherhood portrayed in Amanda Coogan’s performance art - Moreira Eufrausino, Caroline (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
n 1922, Ireland conquered its independence from the British rule and adopted some policies that would shape its national identity. During the Irish nationalist period, women had their role defined as homemaker, mother and wife who would be restricted to the private realm of society while men would take care of the public affairs. To this extent, contraceptive methods and divorce where not allowed. After the feminist movements during the 60s, women have managed to break through barriers that locked them to the private sphere of society and advances have been achieved in relation to the Irish law. However, abortion rights, for example, were not allowed until last year, even in cases when the mother's life was at risk. Taking that into account, this article looks at the work of the Irish performer artist, Amanda Coogan, explains her context and the way she uses her body as a work of art and analyzes the sacred- profane woman inside its dichotomy in contemporary society in Ireland.